Analisis Determinan Faktor yang Berhubungan dengan Kejadian Kurang Energi Kronik (KEK) pada Ibu Hamil di Wilayah Gunung Sindur, Bogor - Avliya Quratul Marjan; Antania Hermada Aprilia; Iin Fatmawati (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2021)
Chronic Energi Deficiency (CED) is a nutritional problem in pregnant women with a prevalence of 17,3% based on Indonesia Basic Health Research or Riset Kesehatan Dasar (Riskesdas) in 2018. Based on age groups, pregnant women who experienced the highest CED were 15-19 years (38,5%). So it is very important to know what factors are related to CED in pregnant women. The purpose of this study was to analyze determinants factors with the incidence of chronic energy deficiency in pregnant women at Gunung Sindur Bogor. This study was an observational study with a cross-sectional approach. Respondents in this study were 70 pregnant women who were selected by purposive sampling. Bivariate analysis was performed using the Chi-Square test and logistic regression for Multivariat analysis. The bivariate analysis showed that there were a relationship between age (p = 0.009), parity (p = 0.027) nutritional knowledge (p = 0.045), energy intake (p = 0.001), and protein intake (p = 0.007) with the incidence of CED in pregnant women. The multivariat results show that energy intake is the most dominant factor associated with the incidence of CED (p = 0.001) in pregnant women at Mount Sindur Bogor.